2016
DOI: 10.1002/pssa.201600158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of free surfaces on microstructure evolution of radiation damage in Fe from molecular dynamics and object kinetic Monte Carlo calculations

Abstract: The influence of surfaces on the evolution of damage of irradiated Fe is studied using object kinetic Monte Carlo with input from molecular dynamics simulations and ab initio calculations. Two effects are analysed: the influence of traps and the initial distribution of damage in the cascade. These simulations show that for a trap concentration of around 100 appm, there are no significant differences between defect concentrations in bulk and thin films. However, the initial distribution of defects plays an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…-The statistics: the data presented in our paper have been obtained with statistics on 1960 80 keV cascades in Fe (for MEND10). Aliaga et al [29] presented the results of 14 cascades in bulk Fe, Byggmastar [23] database contained 50 cascades of 100 keV and Terentyev [30] had 10 cascades per damage energy.…”
Section: Discussion 1) Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…-The statistics: the data presented in our paper have been obtained with statistics on 1960 80 keV cascades in Fe (for MEND10). Aliaga et al [29] presented the results of 14 cascades in bulk Fe, Byggmastar [23] database contained 50 cascades of 100 keV and Terentyev [30] had 10 cascades per damage energy.…”
Section: Discussion 1) Comparison With Literaturementioning
confidence: 99%
“…The PDC capture distance: the data presented in our paper have been obtained with a similar PDC capture distance for SIA and vacancies, taken to be between 2nn and 3nn. Aliaga et al [29] presented the results of 14 cascades in bulk Fe with a PDC capture distance between 1nn and 2nn for both SIA clusters and vacancy clusters, whereas Byggmästar and Sand used (2nn+3nn)/2 for vacancies and (3nn and 4nn)/2 for SIAs [23], i.e. they used a larger PDC capture distance for SIAs than for vacancies.…”
Section: Discussion 1) Comparison With Literaturementioning
confidence: 99%
“…Remarkable progress in elucidating the fundamental origin of structural changes occurring in materials under irradiation has been achieved over the past three decades using molecular dynamics simulations [7,[13][14][15][16]. Simulations primarily explore the production of defects by impacts of energetic particle in the bulk of perfect crystals [17,18] or near surfaces [19,20]. Following the pioneering studies by Samaras et al [21,22], who analyzed how defects were produced by energetic collision events in nanocrystalline materials, extensive computer simulations have been performed exploring the effect of vacancy clusters [23,24], dislocations [25,26], dislocation loops [27], and grain boundaries [28] on defect production and accumulation in materials where the initial microstructure was different from the ideal periodic crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…These models are thus capable of providing relevant information that closer to real materials. However, these simulations require that a large number of parameters (and the way they evolve with temperature) be known accurately, not to mention the impact of surfaces (Aliaga et al 2016) (Duan et al 2018) or the source term, as recently shown in (Jourdan and Crocombette 2018). This means that considerable effort must go into choosing the level of details to enter in the models to minimally perturb the results.…”
Section: Coupling With Other Methodsmentioning
confidence: 99%